Association of alcohol use and dietary lifestyle of commercial drivers during the COVID-19 pandemic in Nigeria - Edo, Great Iruoghene (2023)
A state of equilibrium in which nutrient intake and requirements are balanced is necessary for nutritional health. Two of the most important factors in achieving peak performance are nutrition and hydration. Alcohol is a poor nutrient source for a pre-game meal or hydration since it has been shown to slow one's ability to respond to an opponent or object 72 h after consumption (Kerksick et al. 2018). The assessment of nutritional status is a wide topic, and to be of clinical relevance, the ideal method should be able to detect whether the individual would have high morbidity and mortality in the absence of nutritional support (Bhattacharya et al. 2019). Unfortunately, disease and nutrition combine to lead to secondary malnutrition, or malnutrition may severely affect the underlying condition. Thus, patient outcomes are complex, and trying to construct nutritional effects on outcomes based on single parameters or simplistic models does not take into account the various interactive variables